2004
DOI: 10.5650/jos.53.29
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol Residue - A Rich Source of Glycerol and Medium Chain Fatty Acids

Abstract: Glycerol residue, a by-product of glycerol refining from a palm kernel oil methyl ester plant, was found to be a good source of glycerol and medium chain fatty acids. From analyses of twelve samples, it was found to contain, on average, 20.2 % glycerol and 6.6 % fatty acids. The fatty acids comprised mainly C8:0 (30.3 %), C10:0 (9.4 %) and C12:0 (40.8 %).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
20

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 4 publications
0
17
1
20
Order By: Relevance
“…É composta por glicerol, resíduos de catalisadores, sabão, álcool, monoacilglicerol, diacilglicerol, oligômeros de glicerol e água (Ooi et al, 2004) e apresenta-se na forma de líquido viscoso pardo escuro.…”
Section: Introductionunclassified
“…É composta por glicerol, resíduos de catalisadores, sabão, álcool, monoacilglicerol, diacilglicerol, oligômeros de glicerol e água (Ooi et al, 2004) e apresenta-se na forma de líquido viscoso pardo escuro.…”
Section: Introductionunclassified
“…Similarly, Crespo & EsteveGarcia (2001) reported that the lipid composition of crude vegetable glycerin added to the diet might affect the amount of total abdominal fat and body fat, which may have occurred because of the lipid composition of crude vegetable glycerin. Ooi et al (2004) and Retore et al (2012) indicated that the higher amount of fatty acids in crude glycerin than in semi-purified glycerin might explain the higher deposition of abdominal fat.…”
Section: Resultsmentioning
confidence: 99%
“…Além disso, pode-se obtê-la a partir do processo de transesterificação para produção de biodiesel, com menor grau de pureza, porcentagem de glicerol em torno de 65 a 70% (p/p) e aproximadamente 30% de impurezas como sabão, resíduos de metanol ou etanol, hidróxido de sódio, ácidos graxos livres, mono e diacilglicerol, ésteres, oligômeros de glicerol, MONG (matéria orgânica não-glicerol), polímeros e água. [16][17][18][19] O rápido desenvolvimento da produção de biodiesel no Brasil, impulsionado pelo incremento progressivo de sua participação na composição do diesel comercial (atualmente a proporção é de 93:7 de diesel:biodiesel), afetou diretamente a oferta de bioglicerina no mercado e, por isso, o setor de biodiesel busca um mercado para absorver essa bioglicerina produzida no processo industrial. Boa parte da bioglicerina gerada nas plantas de biodiesel é queimada em fornos e caldeiras para geração de energia calorífica em unidades industriais e, apesar desta atividade ser uma alternativa ambientalmente correta, porque a bioglicerina substitui a lenha e combustíveis fósseis, como óleo combustível e carvão, ela não gera nenhum produto com alto valor agregado.…”
Section: Glicerinaunclassified